Intraoperative Local Anesthesia for Reducing Pain following Tonsillectomy. (23rd August 2013) - Lin, Rui J.; Naidoo, Lalenthra; Burton, Martin J.; Chadha, Neil K.
Abstract : Objectives: Perform a Cochrane review to systematically appraise the available evidence of pain relief through the use of intra‐operative local anaesthetic (LA) administration to the tonsillar region in adults and children undergoing tonsillectomy. Methods: The study followed the rigorous systematic review and meta‐analysis methodology as developed by the Cochrane Collaboration. A comprehensive search strategy was applied to multiple databases for published and unpublished trials up to April 2012. Randomized, double‐blind, placebo‐controlled trials were eligible. Two reviewers independently extracted data and assessed trials for quality. Data analyses were performed using the RevMan 5.1 software. Results: Sixty‐six randomized controlled trials were included in the review. Eleven trials assessing peritonsillar infiltration of LA and seven trials that investigated topical application of LA were suitable for meta‐analysis. Peritonsillar LA infiltration was associated with significant reduction in pain up to 2 hours after surgery (mean difference ‐1.34 on a scale of ‐10 to 10; 95% CI ‐1.80 to ‐0.88; P< 0.00001). Topical LA application to the tonsillar fossa was also associated with significant pain reduction in the early post‐operative period (mean difference ‐0.66 on a scale of ‐1 to 1; 95% CI ‐1.06 to ‐0.27; P = 0.001). Intra‐operative LA was associated with a longer period of time without analgesic requests post‐operatively (mean difference 12 minutes; 95% CI 2.0 to 21.8; P = 0.020). Conclusions: Based on the available evidence, we would advocate routine intra‐operative application of LA, whether infiltrative or topical, for patients undergoing tonsillectomy.